Microstructure and chemorheological behavior of whipped cream as affected by rice bran protein addition. Issue 2 (28th January 2019) - Ghorbani‐HasanSaraei, Azade; Rafe, Ali; Shahidi, Seyed‐Ahmad; Atashzar, Azin
Abstract: The effect of rice bran protein (RBP) isolate addition on the rheological and structural properties of commercial whipped cream with 25% and 35% fat was investigated. Results showed that increasing the fat content from 25% to 35% leads to an increase in the elastic modulus. Furthermore, by increasing the amount of RBP from 1% to 3% in both creams, significant increase occurred in the complex modulus. As the fat content increased from 25% to 35%, the slope of flow behavior was increased, which revealed more thinning behavior and pseudoplasticity index of cream. The cream containing 35% fat and 3% RBP had also shown the low index ( n = 0.298) which confirmed the firmer structure of the cream. The maximum consistency index ( k ) obtained was 9.41 for the cream with 35% fat and 3% RBP, which approved its strong foam structure. In general, according to our results it is obvious that whipped cream with the highest amount of fat and the lowest value of protein can lead to maximum stability of the whipping cream. Among the samples, the lowest stiffness was observed in cream of 35% fat, containing 3% rice bran protein. However, cream containing 35% fat and 1% RBP had convenient overrun and good stability. The microstructural results showed that the cream structure has relatively large globular aggregates in network and develops large pores, which permit to retain sufficient water/air. By increasing the fat content of cream from 25% to 35%, the voids and spaces in the cream were significantly decreased and the pores become less which improve the foam structure. Therefore, it can be concluded the cream with more fat has the more overrun and stability. In general, it is possible to improve the foam structure of cream by substituting fat by RBP. Abstract : Effect of rice bran protein isolate addition on the rheological and structural properties of commercial whipped cream with 25% and 35% fat was investigated. Results showed that increasing the fat percentage from 25% to 35% leads to an increase in the elastic modulus. Furthermore, by increasing the amount of RBP from 1% to 3% in both creams, significant increase occurred in the complex modulus. As the fat content increased from 25% to 35%, the slope of flow behavior was increased, which revealed more thinning behavior and pseduoplasticity index of cream. The cream sample containing 35% fat and 3% RBP had also shown the low index ( n = 0.298) which confirmed the firmer structure of cream. The maximum K obtained was 9.41 for the cream with 35% fat and 3% RBP which approved its strong foam structure.